Adopsi E-Commerce UMKM sebagai Upaya Adaptasi Perubahan Perilaku Konsumen - Rachmawati, Meida (Jurnal EMT KITA, 2024)
The purpose of this study is to evaluate the role that e-commerce plays in promoting growth and profitability in Indonesia's micro, small, and medium-sized enterprise (UMKM) sector. This study applies exploratory and exploratory research methods as well as strategies that support the role of e-commerce in advancing UMKM in Indonesia. The research results indicate that e-commerce has a positive impact on improving customer service quality and making it easier for customers to access product information provided by UMKM.